Thermal Energy Battery With Nano-Enhanced PCM 2019
DOI: 10.5772/intechopen.80574
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Enhancement Technique of PCMs and Its Lattice Boltzmann Modeling

Abstract: Phase change materials (PCMs) have several advantages for thermal energy storage due to their high energy storage density and nearly constant working temperature. Unfortunately, the low thermal conductivity of PCM impedes its efficiency of charging and discharging processes. To solve this issue, different techniques are developed to enhance the heat transfer capability of PCMs. In this chapter, the common approaches, which include the use of extended internal fins, porous matrices or metal foams, high thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 166 publications
0
2
0
Order By: Relevance
“…Sathaiah et al in [17] studied the connection between the foams morphology and thermal conductivity in foams created via the salt space holder method. Qu in [18] researched different techniques to enhance the heat transfer capability of phase change materials (PCMs), comparing metal foams to different solutions. Tian and Zhao in [19] have used open-pore metal foams as heat exchangers in a numerical investigation of phase change materials heat transfer abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Sathaiah et al in [17] studied the connection between the foams morphology and thermal conductivity in foams created via the salt space holder method. Qu in [18] researched different techniques to enhance the heat transfer capability of phase change materials (PCMs), comparing metal foams to different solutions. Tian and Zhao in [19] have used open-pore metal foams as heat exchangers in a numerical investigation of phase change materials heat transfer abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Among different ways to improve the heat transfer within PCM, the following so-called thermal conductivity enhancers can be distinguished: the addition of graphite fiber preforms, porous matrices, nanofillers (graphite, Cu, graphene), silica or alumina catalysts [1][2][3], PCM micro-or macro-encapsulation with organic or metal shells [4,5] or immersing highly thermally conductive complex metal structures within the PCM [6][7][8][9][10]. Such structures (e.g., metal foams (i.e., Al, Cu, FeCrAlY [11]), pipes, plate-fin and pin-fin structures (i.e., steel, Al, Cu) or honeycomb-shaped inserts) can be applied in a form of compact heat exchangers due to their high heat transfer surface area per unit volume and lead to the altered heat flow, enhancing the mixing and fluid dynamics and especially strengthening the thermal conduction and convection. Tao et al, investigating the performance of metal foams/paraffin composite PCM, found out that reducing the Materials 2020, 13, 415 2 of 11 foam cells' size enhances strongly the conduction heat transfer while simultaneously limiting the convection.…”
Section: Introductionmentioning
confidence: 99%